Ionic conductivity of a single porous MnO2 mesorod at controlled oxidation states1. Issue 24 (28th June 2015) - Plett, Timothy; Gamble, Trevor; Gillette, Eleanor; Lee, Sang Bok; Siwy, Zuzanna S.
<x xml:space="preserve">Abstract</x> The ionic conductivity of porous MnO2 at the nanoscale is not well understood, despite possible importance in battery charging/discharging processes.